2020
DOI: 10.1371/journal.pone.0232708
|View full text |Cite
|
Sign up to set email alerts
|

A detailed insight in the high risks of hospitalizations in long-term childhood cancer survivors—A Dutch LATER linkage study

Abstract: ☯ These authors contributed equally to this work. ¶ Membership of the Dutch LATER Study Group for burden of disease includes the listed coauthors and additional consortium members, as listed in the Acknowledgments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 32 publications
3
10
0
Order By: Relevance
“…In the without treatment/surgery only group, 3% of CCS who developed symptomatic cardiac ischaemia, developed it before 30 years of age. Streefkerk et al 26 and Gudmundsdottir et al 27 compared the hospitalisation rate for ischaemic heart disease between a cohort of childhood cancer survivors and a matched general population and found a relative rate of 1.6 and 1.7 (95% CI 1.5 to 1.9), respectively, which are in line with our result. Gudmundsdottir et al also found a larger difference in the younger age groups (aged 20-50 years).…”
Section: Discussionsupporting
confidence: 91%
“…In the without treatment/surgery only group, 3% of CCS who developed symptomatic cardiac ischaemia, developed it before 30 years of age. Streefkerk et al 26 and Gudmundsdottir et al 27 compared the hospitalisation rate for ischaemic heart disease between a cohort of childhood cancer survivors and a matched general population and found a relative rate of 1.6 and 1.7 (95% CI 1.5 to 1.9), respectively, which are in line with our result. Gudmundsdottir et al also found a larger difference in the younger age groups (aged 20-50 years).…”
Section: Discussionsupporting
confidence: 91%
“…That children who survive ALL tend to have higher mortality and morbidity in later life, including subsequent cancers and a wide range of other therapy-related conditions (table 1), is established 4–7. With respect to the latter, however, much of the information on late effects among survivors has come either from analyses of hospitalisations or from questionnaires completed by consenting individuals 8–17. As is evident from the studies summarised in table 1 (which includes those that examined all leukaemias combined and those that also included young adults), less attention has been paid to chronic conditions that do not require hospital admission,7 18–20 and to morbidity patterns that change over time 7 12 21…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] With respect to the latter, however, much of the information on late effects among survivors has come either from analyses of hospitalisations or from questionnaires completed by consenting individuals. [8][9][10][11][12][13][14][15][16][17] As is evident from the studies summarised in table 1 (which includes those that examined all leukaemias combined and those that also included young adults), less attention has been paid to chronic conditions that do not require hospital admission, 7 18-20 and to morbidity patterns that change over time. 7 12 21 The longitudinal data examined in this report contain information on hospital outpatient attendances, as well as inpatient episodes, cancer registrations and deaths.…”
Section: Introductionmentioning
confidence: 99%
“…[5] In another long-term follow-up cohort, abdominopelvic radiotherapy was associated with an increased risk of hospitalization, among other causes due to endocrine, nutritional and metabolic diseases (relative hospitalization rate (RHR) 2.5), as well as subsequent neoplasms (RHR 1.7). [6] In paediatric literature, associations between RT and late toxicity have historically been based on prescribed dose to the target volume. However, for adequate quantification of toxicity, normal tissue complication probability (NTCP) data is required, describing the relation between radiation dose to a tissue in relation to the endpoint (toxicity) of interest.…”
Section: Introductionmentioning
confidence: 99%